ASSESMEN PSIKOLOGIS ANAK DALAM PENGEMBANGAN IEP BERBASIS NILAI-NILAI ISLAM - Laily Abida (Al-Mudarris: Journal Of Education, 2026)
Inclusive education in Indonesia started in 1991 and continue to developt with many problem and solution. The aim of the research to knowing and analyzing psychological assessment for children with soecial needs to find IEP Islamic strategic in school. This research have qualitative approach with case study type of research. Researcher need to explain about every process and implemetation detailing. The result explain that psychological assessment the one is important step for IEP development and how to mapping and diagnose student disability especially for Islamic education. Subject for this research is student with kognitif disability, Learning disability, language and Communication obstacle and Sosial-Emotional Adjusment. Islam have an attention about education for all people without exeption, without limit and obstacles to fulfilll education needs. Found the impact is significanly helpful to develop learning programe for students through the potential that is possessed. The conclusion is inclusive education have many stages that have to completing to make an effective education progress.